HUBUNGAN ANTARA INTELEGENSI DENGAN EFIKASI DIRI PADA SISWA KELAS VII SMP NEGERI “X” KOTA BOGOR - Karisma Riskinanti; Heni Widya Ningrum (Universitas Mercu Buana Jakarta, 2019)
This research aims to determine the relationship between Intelligence and Self-Efficacy of 7th grade students in X junior high school Bogor. This study is quantitative approach. Population in this research is 228 students. The sample is 150 students use from Slovin and purposive sampling methods. Self-Efficacy Questionnaire for Children used in this research. Correlation test result uses pearson correlation show that there is no correlation between IQ and self-efficacy. This can be caused by socio-economic factors that can inhibit the relation between Intellegence and self-efficacy.